A simple feasible alternative procedure to estimate models with high-dimensional fixed effects - Paulo Guimar\~aes; Pedro Portugal (Institute for the Study of Labor (IZA), 2009)
In this paper we describe an alternative iterative approach for the estimation of linear regression models with high-dimensional fixed-effects such as large employer-employee data sets. This approach is computationally intensive but imposes minimum memory requirements. We also show that the approach can be extended to non-linear models and potentially to more than two high dimensional fixed effects.
urn:nbn:de:101:1-2009020957
Keywords: C01; C81; 330; High dimensional fixed effects; linked employer-employee data; Regression; Schätztheorie; Statistische Erhebung; Arbeitsmarktstatistik; Theorie